Catalyst-dependent selectivity in the relay catalytic branching cascade - Bansode, Avinash H.; Shaikh, Aslam C.; Kavthe, Rahul D.; Thorat, Shridhar; Gonnade, Rajesh G.; Patil, Nitin T. (Chemistry-A European Journal, 2015)
The synthesis of small organic molecules as probes for discovering new therapeutic agents has been an important aspect of chemical biology. One of the best ways to access collections of small molecules is to use various techniques in diversity-oriented synthesis (DOS). Recently, a new form of DOS, namely relay catalytic branching cascades (RCBCs), has been introduced, wherein a common type of starting material reacts with several scaffold-building agents (SBAs) to obtain structurally diverse molecular scaffolds under the influence of catalysts. Herein, the RCBC reaction of a common type of substrate with SBAs is reported to give two different types of molecular scaffolds and their formation is essentially dependent on the type of catalyst used.
Keywords: alkynols; cascade synthesis; chemoselectivity; diversity-oriented synthesis; Homogeneous catalysis

Scandium triflate catalyzed unexpected cleavage of C-C bonds in ynones - Kavthe, Rahul D.; Bansode, Avinash H.; Patil, Nitin T. (Arkivoc, 2016)
An unexpected C-C bond cleavage in ynones in the presence of catalytic amounts of Sc(OTf)(3) in methanol under microwave irradiation has been discussed. The effect of substituent on the regioselectivity of C-C bond cleavage has carefully been addressed by employing various ynones derivatives. The mechanism has been proposed for the observed regioselectivity.
Keywords: C-C bond cleavage; Esters; Ketones; scandium triflate; ynones

Catalytic branching cascades in diversity oriented synthesis - Bansode, Avinash H.; Chimala, Prathyusha; Patil, Nitin T. (ChemCatChem, 2017)
Diversity oriented synthesis (DOS) aims to generate small molecules with great structural diversity in an efficient manner. Recent years have witnessed significant achievements in the field, which help to validate the usefulness of DOS as a tool for the discovery of novel, biologically interesting small molecules. Catalytic branching cascades have emerged as a promising strategy because of their potential to transform a common type of substrate into diverse and distinct molecular frameworks. The details of the concept are presented herein.

Effective degradation of organic water pollutants by atmospheric non-thermal plasma torch and analysis of degradation process - Bansode, Avinash H.; More, Supriya Eknath; Siddiqui, Ejaz Ahmad; Satpute, Shruti; Ahmad, Absar; Bhoraskar, Sudha V.; Mathe, Vikas L. (Chemosphere, 2017)
The paper reports the use of atmospheric non-thermal plasma torch as a catalyst for degradation of various organic pollutants dissolved in water. A flow of He mixed with air was used to produce the dielectric barrier discharge (DBD), at the tip of the torch, using pulsed electric excitation at 12 kV. The torch, operated at a power of 750 mW/mm², was seen to completely degrade the aqueous solutions of the pollutants namely methylene blue (MB), methyl orange (MO) and rhodamine-B (RB), at around 10⁻⁴ M concentrations, the concentration of polluants is one order higher than of routinely used heterogeneous photocatalytic reactions, within 10 min of irradiation time at room temperature. UV Visible spectra of the organic dye molecules, monitored after different intervals of plasma-irradiation, ranging between 1 and 10 min, have been used as tools to quantify their sequential degradation. Further, instead of using He, only air was used to form plasma plume and used for degradation of organic dye which follow similar trend as that of He plasma. Further, Liquid Chromatography Mass Spectroscopy (LCMS) technique has been used to understand degradation pathway of methylene blue (MB) as a representative case. Total organic carbon (TOC) measurements indicates significant decrease in its content as a function of duration of plasma exposure onto methylene blue as a representative case. Toxicity studies were carried out onto Gram negative Escherichia coli. This indicated that methylene blue, without plasma treatment, shows growth inhibition, whereas with plasma treatment no inhibition was observed.

Intramolecular ipso-arylative cyclization of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts through merged gold/visible light photoredox catalysis - Bansode, Avinash H.; Shaikh, Samir R.; Gonnade, Rajesh G.; Patil, Nitin T. (Chemical Communications, 2017)
A visible-light-promoted merged gold/photoredox catalyzed ipsoarylative cyclization has been reported. For instance, the reaction of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts in the presence of catalytic amounts of [(4-OCH3)C6H4](3)PAuCl and Ru(bpy)(3)(PF6)(2) under irradiation using a 32WCFL bulb gave arylated spirocarbocycles in moderate to good yields.

Palladium-catalyzed oxidative annulation of pyrrolylalkyl-1H-azoles: towards the synthesis of polyheterocyclic arenes - Tripathi, Krishna N.; Bansode, Avinash H.; Singh, Ravi P. (Synthesis-Stuttgart, 2020)
A highly efficient and regioselective palladium-catalyzed annulation protocol for a series of linear and terminally substituted 1,2- and 1,3-di(heteroaryl)alkanes to the corresponding polyheterocyclic arenes is reported. Herein, intramolecular oxidative coupling involving double C(sp(2))-H bond functionalization provides a feasible access to biheteroaryl systems annulated to a six-membered ring. The methodology is not restricted to six-membered annulations and was extended to the synthesis of compounds with a seven-membered ring and biheteroaryl core.
Keywords: C-H functionalization; imidazoles; oxidative coupling; Palladium; pyrroles